The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1016/j.jad.2007.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms and antidepressant use in a random community sample of ethnically diverse, urban elder persons

Abstract: BACKGROUND-There are limited data on depressive symptoms and antidepressant use in ethnically diverse, urban elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
28
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 25 publications
(20 reference statements)
2
28
1
1
Order By: Relevance
“…In most studies in other countries, lower income or lower educational attainment was associated with a lower prevalence of depression treatment, or there was no association [22][23][24][25][26]. In the present study, however, the lowestincome quintile showed the highest rate of depression treatment among respondents with psychological distress.…”
Section: Discussioncontrasting
confidence: 73%
“…In most studies in other countries, lower income or lower educational attainment was associated with a lower prevalence of depression treatment, or there was no association [22][23][24][25][26]. In the present study, however, the lowestincome quintile showed the highest rate of depression treatment among respondents with psychological distress.…”
Section: Discussioncontrasting
confidence: 73%
“…The rate of mental health service use for depression treatment by the KA elders in our study was found to be seeking professional help among elders with clinically significant depression in the Washington Heights-Inwood Columbia Aging Project (Grunebaum, Oquendo, & Manly, 2008) or the antidepressant treatment rate of 35.7% among depressed elderly participants in the Cache County study (Steffens, Fisher, Langa, Potter, & Plassman, 2009). Though scarce, a few available national data indicate Asian American elders as one of the least likely ethnic groups to utilize mental health services.…”
Section: Discussionmentioning
confidence: 67%
“…A higher z-score indicates better cognitive performance. A more complete description of the neuropsychological test battery and the cognitive scores can be found in previous publications (Stern et al ., 1992; Manly et al ., 2005; Grunebaum et al ., 2008; Salthouse, 2011; Zahodne et al ., 2014). …”
Section: Methodsmentioning
confidence: 99%